A critical ethnographic perspective on risk and dangerousness in forensic psychiatry. Issue 2 (1st September 2022) - Domingue, Jean‐Laurent; Jacob, Jean‐Daniel; Perron, Amélie; Pariseau‐Legault, Pierre; Foth, Thomas
Abstract: In the Canadian forensic psychiatric context, the concepts of risk and dangerousness interact, intersect, and morph into the notion of significant threat to the safety of the public . Stemming from the results of a critical ethnography of the Ontario Review Board, this article unpacks the central role of forensic psychiatric nursing, as an example of a 'psych' discipline (e.g., psychiatry and psychology), in a system that is built to produce risky persons and to legitimize their detention and supervision. By using excerpt of interviews conducted with nurses, ethnographic observations of Review Board hearings, and other documentary artifacts, the findings illustrate how rationalizations of risk and dangerousness are contingent on space, time, and observer. Depending on the time of the assessment or on the health‐care professional who performs it, different elements including, but not limited to, mental illness, interpersonal relationships, financial instability, and sexual vulnerability, are relied upon in very fluid, interchangeable, and discretionary ways to justify findings of dangerousness. Such a dynamic expands the reach of psychiatry's legitimacy at identifying risky conduct and controlling risky persons to domains very loosely associated with the notion of dangerousness. The work of Foucault and Castel provides the theoretical backdrop on which rests the discussion and the implications for nursing.